Enhancing english speaking skills A2 CEFR level through afro-ecuadorian oral traditions Proposal: development an english educational booklet focused on afro-ecuadorian oral traditions enhancing speaking skills A2 CEFR level. - García Gonzales, Angie Nicole (2024)
PDF